Practical woodcarving and gilding - Hayward, Charles H; Wheeler, William (London : Bell & Hyman, 1983)
Contiene: tools and equipment, sharpening the tools, handling the tools, drawing and design, exercise in handling tools, simple tool cuts, heraldic lion, roundel, acanthus leafage, carved mouldings, linenfold panel, trays with pie-crust edgings, gothic carving, gilt electric lamp polished and gilt elliptical frame, lettering, carving in the roundgilding tools and materials, gilding the practical work, timbers for woodcarving